Characterizing the astrometric quality of AGNs in Gaia-CRF3 - Liao, S. (2025)
AGNs, due to their vast distances and small apparent sizes, play a crucial role in defining the celestial reference frame. With approximately 1.9 million AGNs observed in the visible spectrum in Gaia DR3 and a precision comparable to radio wavelengths, Gaia’s astrometric measurements provide a foundation for constructing the next-generation kinematically non-rotating reference frame in optical wavelength, using AGNs as primary reference sources [1], Accurately assessing the systematic residuals in quasar astrometry is essential for fundamental astronomy. Therefore, refining the AGN catalog from Gaia is crucial. This study aims to characterize systematic errors in the parallaxes and proper motions of AGNs in Gaia DR3, exploring correlations between these errors and various AGN properties reported by Gaia and other sources [2], Additionally, a substantial number of AGNs in Gaia-CRF3 exhibit significant astrometric offsets despite their confirmed extragalactic nature. Our analysis reveals that these anomalies primarily stem from dual AGNs and lensed quasars, where structural variations cause photo-center jitter, mimicking parallax and proper motion [3]. With milliarcsecond-level precision, such sources must be rigorously identified and excluded from reference frame construction. To address this, an astrometric quality index is introduced for each source. Our preliminary results demonstrate a clear correlation between declining astrometric index values and increasing positional, proper motion, and parallax errors, validating this classification as a key metric for identifying high-quality primary reference sources.